2010
DOI: 10.1088/0029-5515/50/11/115004
|View full text |Cite
|
Sign up to set email alerts
|

Damage to nearby divertor components of ITER-like devices during giant ELMs and disruptions

Abstract: During normal operation of the high confinement mode in future ITER devices, edge-localized modes (ELMs) are a potential threat to the divertor components lifetime and plasma contamination. To predict the outcome of the direct ELM plasma impact on the divertor plate, conversion of plasma energy into radiation in the shielding layer, and then the resulting energy deposition of radiation flux to the surrounding areas, comprehensive physical and numerical models are developed and implemented in the HEIGHTS packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
(60 reference statements)
0
24
0
Order By: Relevance
“…Our previous study of this secondary plasma showed significant conversion of the incident disrupting plasma particle energy to photon radiation to several nearby components. 5,10 Contrary to the main core plasma, the secondary divertor plasma is much denser, colder, heavier, and not fully ionized. The MHD of the generated secondary plasma dominates the divertor space, i.e., the impact of the D/T plasma during the loss of core confinement can be considered as a small perturbation and an energy source feeding this evolving plasma.…”
Section: -2mentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study of this secondary plasma showed significant conversion of the incident disrupting plasma particle energy to photon radiation to several nearby components. 5,10 Contrary to the main core plasma, the secondary divertor plasma is much denser, colder, heavier, and not fully ionized. The MHD of the generated secondary plasma dominates the divertor space, i.e., the impact of the D/T plasma during the loss of core confinement can be considered as a small perturbation and an energy source feeding this evolving plasma.…”
Section: -2mentioning
confidence: 99%
“…Taking into account the scaling and selection rules, the average parameters of ITER tokamak transient events of the edge localized modes (ELMs) and disruptions were estimated. [3][4][5] Predictions of these transient event parameters vary in the literature. For example, the most common approaches 4 predict for ITER design that the pedestal energy W ped ¼ 105 MJ and plasma temperature of pedestal T ped ¼ 3.3 keV with frequency 1 -100 Hz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooling profile of the preheated layer should be distorted due to the variations in media properties. In the absence of analytical solutions in this case, we compared our calculations with the implicit method, since it has similar error magnitude to our Monte Carlo method and is also currently being used in the MHD integrated package [31]. The comparison shown in Figure 7b between the implicit and Monte Carlo methods demonstrates good agreement for the nonhomogeneous media conditions.…”
Section: Sizyuk and A Hassaneinmentioning
confidence: 96%
“…Our last 1-D benchmarking was carried out to prove that the developed Monte Carlo model is also valid within the range of real MHD plasma conditions needed for the integrated simulation of magnetic fusion devices [31]. In real plasma, the transport coefficients depend nonlinearly on the local temperature, and the behavior=stability of the numerical methods under these conditions is important.…”
Section: Sizyuk and A Hassaneinmentioning
confidence: 99%